1998
DOI: 10.1007/s000180050187
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between action potential, contraction-relaxation pattern, and intracellular Ca 2+ transient in cardiomyocytes of dogs with chronic heart failure

Abstract: Abnormalities of contractile function have been identified in cardiomyocytes isolated from failed human hearts and from hearts of animals with experimentally induced heart failure (HF). The mechanism(s) responsible for these functional abnormalities are not fully understood. In the present study, we examined the relationship between action potential duration, pattern of contraction and relaxation, and associated intracellular Ca2+ transients in single cardiomyocytes isolated from the left ventricle (LV) of dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…The ratio between amplitudes of the spike and dome phases was suggested to be an index for the severity of HF (Gwathmey et al, 1987). Similar to the shape of abnormal contraction, abnormally prolonged Ca 2+ transients have also been observed in both ventricular muscle strips (Gwathmey et al, 1987) and cardiomyocytes isolated from failing hearts (Beuckelmann and Erdmann, 1992;Maltsev et al, 1998b) (Fig.10A). At the higher frequencies, these abnormalities account for the reversal of the force-frequency relationship in failing myocardium, leading to an increase in diastolic [Ca 2+ ] i and diastolic tension (Fig.10B "Control") (Feldman et al, 1988;Undrovinas et al, 2006).…”
Section: Blockade Of I Nal Improves Ca 2+ Transient and Contractilitymentioning
confidence: 84%
See 1 more Smart Citation
“…The ratio between amplitudes of the spike and dome phases was suggested to be an index for the severity of HF (Gwathmey et al, 1987). Similar to the shape of abnormal contraction, abnormally prolonged Ca 2+ transients have also been observed in both ventricular muscle strips (Gwathmey et al, 1987) and cardiomyocytes isolated from failing hearts (Beuckelmann and Erdmann, 1992;Maltsev et al, 1998b) (Fig.10A). At the higher frequencies, these abnormalities account for the reversal of the force-frequency relationship in failing myocardium, leading to an increase in diastolic [Ca 2+ ] i and diastolic tension (Fig.10B "Control") (Feldman et al, 1988;Undrovinas et al, 2006).…”
Section: Blockade Of I Nal Improves Ca 2+ Transient and Contractilitymentioning
confidence: 84%
“…It was shown that a partial I NaL inhibition and/or acceleration of I NaL decay rescue normal repolarization, decrease beat-to-beat AP duration variability, and improve Ca 2+ handling and contractility of the failing cells (Maltsev et al, 1998b;Maltsev et al, 2007;Undrovinas et al, 2006;Undrovinas et al, 1999). Thus, I NaL has emerged as a novel target for cardioprotection to treat the failing heart Maltsev et al, 2001;Noble and Noble, 2006).The focus of this review is to summarize the available data from experiment and numerical modeling of I NaL in normal and failing myocardium in order to integrate I NaL into the established electrophysiological and Ca 2+ regulation mechanisms in normal and failing cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6), 2) decrease beat-to-beat APD variability, and 3) improvement of Ca 2ϩ handling and contractility (22,25,41,42,44). Accordingly, I NaL has emerged as a novel target for cardioprotection to treat the failing heart (24,26,34).…”
Section: Physiological Significancementioning
confidence: 99%
“…14 Cardiomyocyte contraction and relaxation were recorded using an edge detection algorithm. 15 Contraction was evoked by electrical field stimulation at a frequency of 1.0 Hz. Percent cardiomyocyte shortening, peak velocity of shortening, and peak velocity of relengthening were measured in 5 to 10 cardiomyocytes from each dog selected at random.…”
Section: Contraction and Relaxation Of Isolated Cardiomyocytesmentioning
confidence: 99%